"We are mama and papa bears": A qualitative study of parents' adaptation process during transition to adulthood. (November 2020) - Wong, Venus; Ruble, Lisa; Brown, Laura
Highlights: Parents of autistic youths/young adults found insufficient transition-related support. Parents of autistic youths/young adults had their own goals and dreams for themselves. Parents of autistic youths/young adults found meaning in caregiving. Abstract: This qualitative study aimed to understand the stressors, external and internal support, coping strategies, and family adaptation outcomes during transition, from a parent's perspective, using the ABCX model (McCubbin & McCubbin, 1993). Thirteen parents of adolescents and young adults with ASD were interviewed. These parents reported a continually high level of stress due to normative strains and ASD-related demands. They described the tangible, emotional, informational, and internal resources received and needed. Parents, as active agents in their children's lives, have their own views towards transition, philosophy, and ways of coping. Even though many of them reported negative experiences, these parents also found new meanings and happiness in their lives. This study detailed the adaptation process during transition.